DEVELOPMENT OF RITONAVIR LOADED NANOPARTICLES: IN VITRO AND IN VIVO CHARACTERIZATION - Patil, Pravin S; Dhawale, Shashikant C (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The purpose of the present investigation was to develop a nanosuspension to improve dissolution rate and oral bioavailability of ritonavir. Methods: Extended-release ritonavir loaded nanoparticles were prepared using the polymeric system by nanoprecipitation technique. Further, the effect of Eudragit RL100 (polymeric matrix) and polyvinyl alcohol (surfactant) was investigated on particle size and distribution, drug content, entrapment efficiency, and in vitro drug release from nanosuspension where a strong influence of polymeric contents was observed. Drug-excipient compatibility and amorphous nature of drug in prepared nanoparticles were confirmed by Fourier transform infrared spectroscopy, differential scanning calorimetry, and powder X-ray diffraction studies, respectively. Results: Hydrophobic portions of Eudragit RL100 could result in enhanced encapsulation efficiency. However, increase in polymer and surfactant contents lead to enlarged particle size proportionately as confirmed by transmission electron microscopy. Nanosuspension showed a significant rise in dissolution rate with complete in vitro drug release as well as higher bioavailability in rats compared to the pure drug. Conclusion: The nanoprecipitation technique used in present research could be further explored for the development of different antiretroviral drug carrier therapeutics.